Role of Two-Component System Response Regulator bceR in the Antimicrobial Resistance, Virulence, Biofilm Formation, and Stress Response of Group B Streptococcus - Yang, Ying; Luo, Mingjing; Zhou, Haokui; Li, Carmen; Luk, Alison; Zhao, GuoPing; Fung, Kitty; Ip, Margaret (Frontiers in Microbiology, 2019)
Group B Streptococcus (GBS; Streptococcus agalactiae) is a leading cause of sepsis in neonates and pregnant mothers worldwide. Whereas the hyper-virulent serogroup III clonal cluster 17 has been associated with neonatal disease and meningitis, serogroup III ST283 was recently implicated in invasive disease among non-pregnant adults in Asia. Here, through comparative genome analyses of invasive and non-invasive ST283 strains, we identified a truncated DNA-binding regulator of a two-component system in a non-invasive strain that was homologous to Bacillus subtilis bceR, encoding the bceRSAB response regulator, which was conserved among GBS strains. Using isogenic knockout and complementation mutants of the ST283 strain, we demonstrated that resistance to bacitracin and the human antimicrobial peptide cathelicidin LL-37 was reduced in the ΔbceR strain with MICs changing from 64 μg/ml and 256 μg/ml to 0.25 μg/ml and 64 μg/ml, respectively. Further, the ATP-binding cassette transporter was upregulated by sub-inhibitory concentrations of bacitracin in the wild-type strain. Upregulation of dltA in the wild-type strain was also observed and thought to explain the increased resistance to antimicrobial peptides. DltA, an enzyme involved in D-alanylation during the synthesis of wall teichoic acids, which mediates reduced antimicrobial susceptibility, was previously shown to be regulated by the bceR-type regulator in Staphylococcus aureus. In a murine infection model, we found that the ΔbceR mutation significantly reduced the mortality rate compared to that with the wild-type strain (p < 0.01). Moreover, this mutant was more susceptible to oxidative stress compared to the wild-type strain (p < 0.001) and was associated with reduced biofilm formation (p < 0.0001). Based on 2-DGE and mass spectrometry, we showed that downregulation of alkyl hydroperoxide reductase (AhpC), a Gls24 family stress protein, and alcohol dehydrogenase (Adh) in the ΔbceR strain might explain the attenuated virulence and compromised stress response. Together, we showed for the first time that the bceR regulator in GBS plays an important role in bacitracin and antimicrobial peptide resistance, virulence, survival under oxidative stress, and biofilm formation.